2004
DOI: 10.1063/1.1668334
|View full text |Cite
|
Sign up to set email alerts
|

The magnetic Weyl calculus

Abstract: In the presence of a variable magnetic field, the Weyl pseudodifferential calculus must be modified. The usual modification, based on "the minimal coupling principle" at the level of the classical symbols, does not lead to gauge invariant formulae if the magnetic field is not constant. We present a gauge covariant quantization, relying on the magnetic canonical commutation relations. The underlying symbolic calculus is a deformation, defined in terms of the magnetic flux through triangles, of the classical Moy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
214
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(218 citation statements)
references
References 26 publications
(36 reference statements)
4
214
0
Order By: Relevance
“…These phases appear very naturally in the continuous case, see [7,8,19,22,23,24,25,26], where it is shown that if a(x) is the transverse gauge generated by a globally bounded magnetic field |b(x)| ≤ 1, then φ(x, x ′ ) can be chosen to be the path integral of a(x) on the segment linking x ′ with x. This is the same as the magnetic flux of b through the triangle generated by x, x ′ and the origin.…”
Section: Previous Results and Open Problemsmentioning
confidence: 99%
“…These phases appear very naturally in the continuous case, see [7,8,19,22,23,24,25,26], where it is shown that if a(x) is the transverse gauge generated by a globally bounded magnetic field |b(x)| ≤ 1, then φ(x, x ′ ) can be chosen to be the path integral of a(x) on the segment linking x ′ with x. This is the same as the magnetic flux of b through the triangle generated by x, x ′ and the origin.…”
Section: Previous Results and Open Problemsmentioning
confidence: 99%
“…It turns out that the integral formula for the product found in [MP04,IMP07] is not amenable to the derivation of an asymptotic expansion in ǫ and λ. Although an asymptotic expansion for ǫ = 1 = λ has been derived in [IMP07], calculating each term has proven to be very tedious and it is not obvious how to collect terms of the same power in ǫ and λ.…”
Section: Equivalence Of Formulas For Magnetic Weyl Productmentioning
confidence: 99%
“…However, we can show the equivalence to the product formula obtained by two of the authors in [MP04] by writing out the symplectic Fourier transforms, RHS of (2.6) = 1…”
Section: Equivalence Of Formulas For Magnetic Weyl Productmentioning
confidence: 99%
“…In the next section we introduce a concrete example of a normal subalgebra F ⊂ L and its extension F * suitable for quantizing the phase space T * M. In the case M = R n similar extensions were used in [15,[61][62][63][64].…”
Section: Mmentioning
confidence: 99%
“…The magnetic algebra generated by relations (1.2) is an interesting and useful object for physical and mathematical applications, [6][7][8][9][10][11][12][13][14][15]. In particular, the case of quadratic magnetic field F represents an example of quadratic quantum algebra (1.2) which corresponds to the symplectic space R 2n of constant non-zero curvature [5].…”
Section: Introductionmentioning
confidence: 99%